Awareness and practices on Municipal solid waste management among students at University Malaysia Kelantan Jeli Campus. Issue 1 (1st November 2022) - Nawawi, S A; Muniandy, I; Fauzi, N M; Nor, A N M; Ibrahim, N; Jamil, R M; Aziz, H A; Nawawi, R; Ya'acob, S H; Nazarie, W N F W M
Abstract : In a world that rapidly rushes towards an urban future, the amount of municipal solid waste (MSW) is increasing drastically compared to the rate of urbanisation. During the early 2000s, around 2.9 billion people produced 0.64 kg of municipal solid waste (MSW) per person per day, but now the amount has increased to 3 billion people generating 1.2 kg per person per day. The waste products produced in higher educational institutions such as colleges and universities equal the operation of large-scale industries and healthcare facilities. Thus, this study was conducted to determine the level of practices and awareness of municipal solid waste management (MSWM) among students in UMK Campus Jeli. Besides, the association between the practices and awareness of municipal solid waste management among students in Universiti Malaysia Kelantan (UMK) Jeli Campus were measured. This study utilised a questionnaire concerning the students' awareness and practices of MSW. The data were analysed using descriptive and chi-square tests. The results showed that the practices of students on MSW in terms of segregation were average, 'reduce' and 'reuse' practices were both high. While 'recycling' and 'disposal' practices were average and low, respectively. However, their awareness of MSWM was high. There was a significant association between awareness and practices regarding segregation, reduce, reuse, recycle and disposal of MSWM. In conclusion, UMK Jeli students have good practice and awareness of Municipal solid waste management. The students should be more persistent in the practices of MSW to live a more sustainable lifestyle.